МАКЕДОНСКИЙ ЯЗЫК И КУЛЬТУРА В АСПЕКТЕ ПЕРЕВОДЧЕСКОЙ И КУЛЬТУРОЛОГИЧЕСКОЙ ПРОБЛЕМАТИКИ (Филологические заметки, 2019)
In this article similar and different features of Macedonian and Russian cultures are discussed. In addition factors conditioned the specific development of the Macedonian language and culture in comparison with the Russian ones are analysed. It is also noted that in spite of similarity of two Slavonic cultures the each one has gone its own way of development and formed in different historical conditions and ethnographical zones. Considering the mentioned facts and cultural approach, the translatorese problematics connected with the Macedonian language and culture as a member of the intercultural communication should be studied from the following points of view: 1) translation from the cognate Slavonic languages and cultures; 2) the complex of common cultural peculiarities, typical of the Balkan linguacultural intercommunity; 3) individual features characterizing the specific development of the Macedonian language, literature and culture. The study of cultural aspects of translation allows to identify the specific furthers of each linking cultures and contribute to their further understanding of each other.